The Holy Bible : translated from the Latin Vulgate, diligently compared with the Hebrew, Greek, and other editions, in divers languages. The Old Testament, first published by the English College at Douai, A.D. 1609; and the New Testament, first published by the English College at Rheims, A.D. 1582. With annotations, references, historical and chronological index, etc. (Dublin : James Duffy & Co., 1865)
The text in double columns, with marginal references and notes arranged in the form of footnotes. With two leaves for family record after the general title page. The Apocrypha followed by an historical and chronological index to the Old Testament. The New Testament followed by an index and tables. Woodcut illustrations in the text.